Family demands of selected micro and small business entrepreneurs in Metro Manila - Laxa, Martha Angelica A. (College of Home Economics, University of the Philippines Diliman, 2015)
This study aimed to identify family demands that have perceived positive and negative influence on different aspects of businesses, and to describe the strategies and resources used by entrepreneurs to cope with these demands. The participants for this study were married female entrepreneurs who have at least one child and own a micro or small business enterprise in Metro Manila. The data was gathered through in-depth interviews using a researcher-made open-ended questionnaire. All gathered information from the interviews were analyzed and explained using content analysis. Results show that the common family demands that have perceived positive influence on the business include purchasing food supplies, maintaining the house, preparing meals for the family, paying household bills, budgeting expenses, spending quality time with the family members, attending family gatherings, and accompanying parents in their medical visits. On the other hand, the common family demands that have perceived negative influence children, clashing goals and opinions as well as pressure from family members to succeed in the business. The different strategies and resources used by entrepreneurs to cope with family demands that influence their business are business-related strategies, family and household-related strategies, self-related strategies, and the use of technology. Recommendations for future researches on work and family demands are provided at the end of this paper.